The association between social cohesion and community resilience in two urban slums of Port au Prince, Haiti. (March 2018) - Patel, Ronak B.; Gleason, Kelsey M.
Abstract: Multiple recent global agendas have advanced the case for resilience to underpin humanitarian action and disaster risk reduction. These agendas have been incorporated into multiple efforts but evidence to guide action has lagged behind. This study examines a specific link, often cited through qualitative research, between social cohesion and community resilience in two urban slums of Port au Prince, Haiti. Scales to measure social cohesion and resilience are applied to these communities to develop a quantitative measure of these two characteristics. These two characteristics are then analyzed with various other demographic variables of community members to quantitatively explore associations among them. The results show that a higher social cohesion score is statistically associated with a higher resilience score and among the variables tested, social cohesion had the greatest impact on the community resilience as measured by these scales. and shows a statistical association between the two. The findings add to the growing but nascent literature on empirical evidence for resilience characteristics. Further examinations are drawn out of the findings and future investigations should tackle the inductively derived characteristics of resilience to further guide programs and policy.